PEMBELAJARAN DI SEKOLAH: HARAPAN DAN KENYATAAN - Prabowo, Mulyo (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Schools are the educational institution that exists hundred centuries ago. It isbegun with only an activity to fill a leisure time for children of Roman’s aristocrats. In the next development, schools become an institution designed to teach students under teachers’ supervision. Most countries have formal education system where school is as an obligation for everyone on their age. Schools as a system include some components and its components consist of some factors. Each factors are related and forming a system.Schooling system in some countries has their own unique and characteristics, include in Indonesia’s school institution. The expectation of family, society, and nation toward school institutions are truly tremendous, which is forming each individual to be an intelligent and smart person.Schools are the communities’ only expectation to form such things;however, some policies and schools’ problems are very complex and complicated. Therefore, it needs deep thinking and diagnoses comprehensively in order to make school institutions get closer to family, society, and nation’s expectation.